2017
DOI: 10.1021/acs.jafc.7b00770
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Specificity Immunoassay for Simultaneous Detection of Ochratoxins A, B, and C in Millet and Maize

Abstract: Ochratoxins A, B, and C (OTA, OTB, and OTC) can be found in cereals and feeds; the simultaneous detection of these ochratoxins holds a great need in food safety. In this study, four antibodies raised from two ochrotoxin haptens and two coating antigens were compared, and then a sensitive and broad-specificity enzyme-linked immunosorbent assay (ELISA) was established for the simultaneous determination of three ochratoxins, where the detection limits were 0.005, 0.001, and 0.001 ng/mL for OTA, OTB, and OTC, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…2c-d. BSA and OVA have the maximum absorption peak at 280 nm, and RB has a maximum absorption peak at 553 nm, while the characteristic absorption peaks of the conjugate RB-BSA and RB-OVA were at 565 nm, which differed significantly from the spectrogram of RB, and BSA/OVA, indicated that the coupling of RB-BSA/OVA was successful [25]. Similar analysis was carried out for RBITC-BSA/OVA, and therefore, the coupling of RBITC-BSA/OVA was confirmed to be successful.…”
Section: Preparation Of Immunogen and Coating Agsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c-d. BSA and OVA have the maximum absorption peak at 280 nm, and RB has a maximum absorption peak at 553 nm, while the characteristic absorption peaks of the conjugate RB-BSA and RB-OVA were at 565 nm, which differed significantly from the spectrogram of RB, and BSA/OVA, indicated that the coupling of RB-BSA/OVA was successful [25]. Similar analysis was carried out for RBITC-BSA/OVA, and therefore, the coupling of RBITC-BSA/OVA was confirmed to be successful.…”
Section: Preparation Of Immunogen and Coating Agsmentioning
confidence: 99%
“…The generation of pAbs was similar to the previous work [25]. Briefly, two kinds of immunogens, RB-BSA and RBITC-BSA, were injected to the New Zealand rabbits, respectively.…”
Section: Generation Of Pabsmentioning
confidence: 99%
“…In general, the larger the clog P value, the longer the retention time will be in the reversed-phase chromatography system. [26][27][28][29][30] According to the above method, a total of 32 metabolites in vivo and 27 metabolites in vitro (12 metabolites in rat liver microsomes and 20 metabolites in rat intestinal ora) were identied and are shown in Tables 1, 2 and 3, respectively. In addition, the structures of all metabolites are presented in Fig.…”
Section: Analytical Strategymentioning
confidence: 99%
“…The competitive indirect enzymelinked immunosorbent assay (CI-ELISA) was performed according to an ELISA protocol described previously. 22 The 96-well plates were coated with AFB 1 -GA-OVA (100 μL/well), incubated overnight at 37 °C, and then washed twice with PBST solution containing 0.5% Tween-20 in PBS. The plates were then blocked with blocking buffer at 37 °C for 3 h and dried at 37 °C for 1 h. For the negative control wells of the precoated plates, IgY dilutions (50 μL/well) and PBS (50 μL/well) were added.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%